Myositis as a de-novo extraintestinal manifestation of ulcerative colitis in a pediatric patient developing post-colectomy: a case report - Kalēja, Kristīne; Apine, Ilze; Kaže, Inita (International Journal of Contemporary Pediatrics, 2024)
This report presents the case of a 13-year-old female with a history of ulcerative colitis who underwent ileostomy closure after total colectomy. Postoperatively, she developed right leg paresis and extensive swelling of the lower extremities. Imaging investigations revealed myositis with avascular necrosis in the distal femoral condyles. These findings were consistent with myositis as an extraintestinal complication of ulcerative colitis.